Metodologia de análise de implante bioreabsorvível aplicado em coluna lombar utilizando modelagem por elementos finitos e curva de degradação - Souza, Fernando Lourenço de (2011)
Bioresorbable materials, consisting mainly of polymers, have as main components, lactic acid and glycolic acid monomers. These in turn have a function of great interest in biomedical and bioengineering studies, which is the bioresorption process, i.e., the breaking of polymer by hydrolysis into lactic acid and glycolic acid. These monomers are eliminated through body natural cycle called Krebs cycle. This degradation process is directly related to the mass loss, which depending on the polymer composition, has a predetermined time to degrade. This loss of mass over time, promotes a consequent loss of mechanical strength. In surgical procedures, implants made from these materials must withstand the loads imposed until the healing and osteosynthesis process. In this case, the design of these devices has a great importance in the recovery process of patients. Generally, the mathematical models on the degradation process of these materials evaluate molecular weight loss over time and are validated by testing ―in vitro‖ and ―in vivo‖. The objective of this work is to develop a methodology to evaluate the mechanical behavior of devices produced by bioresorbable materials in degradation process using the finite element analysis linked to an multidisciplinary and multi-objective software. The degradation process analysis was implemented and an implant for lumbar interbody fusion (Cage) was evaluated. The Cage was adapted to the lumbar spine set (L3-L4). The numerical analysis showed that while the bone graft wasn t consolidated the displacement are practically restricted by the Cage structure. On the other hand, when the Cage material degrade, the vertebrae fixation is transferred to the bone structure formed by the bone graft in 9 months. Cage lost its structural integrity at about 18 months.